The Local and Global Knowledge Dynamics through Communities. The Case of Communities of Makers and Social Entrepreneurs in Barcelona - Capdevila, Ignasi (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2017)
Previous research has underlined the multiscalar character of the knowledge dynamics that are involved in the localized innovation processes. The article studies two types of communities of practice (CoPs) outside organizations located in Barcelona, by taking a community-based view of their local and global linkages. At the local level, our results show that community members participate in a “local buzz” while engaging in the development of ‘local pipelines’ with other local actors. Similarly, at the global level, local communities exchange knowledge through a “global buzz” generated around networks of practice (NoPs) while creating “global pipelines” with distant actors external to the NoP.